Near fatal puerperal thrombosis on Björk-Shiley mitral valve prosthesis. Issue 8 (August 1978) - McLeod, A A; Jennings, K P; Townsend, E R
Abstract : A 22-year-old woman required emergency mitral valve replacement three weeks post partum because of thrombotic obstruction of her prosthetic mitral valve. Low dose subcutaneous heparin was administered from the 17th week of pregnancy. Though there was a successful fetal outcome, heparin did not prevent thrombosis on the prosthesis and its continuation into the puerperium proved nearly fatal.